Saponins enhance the stability and cost-efficiency of human embryonic stem cell culture - Jingyi Shi; Mei Wu; Shi Fang; Zhuo Liu; Huihui Liu; Ying Zhao; Linlin Liu; Zhicheng Shao (Cell Regeneration)
Abstract The cultivation and differentiation of human embryonic stem cells (hESCs) into organoids are crucial for advancing of new drug development and personalized cell therapies. Despite establishing of chemically defined hESC culture media over the past decade, these media's reliance on growth factors, which are costly and prone to degradation, poses a challenge for sustained and stable cell culture. Here, we introduce an hESC culture system(E6Bs) that facilitates the long-term, genetically stable expansion of hESCs, enabling cells to consistently sustain high levels of pluripotency markers, including NANOG, SOX2, TRA-1–60, and SSEA4, across extended periods. Moreover, organoids derived from hESCs using this medium were successfully established and expanded for at least one month, exhibiting differentiation into cortical organoids, GABAergic precursor organoids and heart-forming organoids. This innovative system offers a robust tool for preserving hESC homeostasis and modeling the nervous system in vitro.